PENGARUH MANAJEMEN SARANA PRASARANA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI INSPEKTORAT KOTA CIMAHI - Deti Hermawati, - (2011)
This research is based on phenomenon of not optimal performance of Inspection Board of Cimahi city, where quantitatively the performance has not shown any progress from year to year. Based on some research examination and theoretical literatures, factors giving effect to motivation of employees are policy of management of facilities which implemented and working motivation which given by chief/supervisor, in order to incresing work performance. Based on the previous explanation, the researcher is interested in conducting a research on the impact of facilities management and work motivation to employee's performances. This research has three variables; two independent variables and one dependent variable. The dependent variables are management of facilities (X1) and work motivation (X2) and the independent variable is work performance (Y1). The methods used are descriptive and explanative. The writer use two kinds of data which is primary and secondary data. The population in this research is the whole 30 (thirty) employees at the Inspectorate Board of Cimahi City. The correlation value is 0.859, this value shows degree of correlation strenght between management of facilities (X1) and work motivation (X2) as a varieble which given an effect to work performance (Y), it's giving contributions about 0.738 or 73.8% respectively. The policy of management of facilities (X1) is 0.506 which given impact to work performance about 0.506 0r 50,6%, with an assumption that motivation level is constant. Then the biggest impact given by work motivation to work motivation is 0.670 or 67.00%, while the degree of effectiveness of the model is 0.738 or 73.8%. Based on the research findings, the writer recommend that the Inspectorate Board of Cimahi City should increase the system of facilities provision to be well organized, and to motivate the employees sustainably in order to achieve the highest level of motivation.